Nurturing the scientific mind: resilience and job satisfaction among Saudi faculty - Asfahani, Ahmed M. (Frontiers in Psychology, 2024)
This study examines the interplay between psychological resilience, job satisfaction and research motivation among teachers at Saudi Arabian universities. Particular attention is paid to the relationship between satisfaction and academic performance and well-being. The data is based on a survey of 321 faculty members, and descriptive statistics and correlations are used. The research instruments included a self-developed scale to measure these constructs, and data analysis was conducted using SPSS software. The findings revealed moderate job satisfaction levels, with a significant correlation between resilience and both job satisfaction and research motivation. Resilience was identified as a key predictor of job satisfaction, especially among professors compared to lecturers. Uniquely focused on the Saudi academic context, this study offers insights into culturally specific factors affecting academic faculty, underscoring the importance of enhancing resilience and satisfaction within academic settings. These implications align with Saudi Arabia's Vision 2030 goals, suggesting targeted strategies to improve faculty well-being and performance.